2022
DOI: 10.33448/rsd-v11i8.30824
|View full text |Cite
|
Sign up to set email alerts
|

Equine asthma in Brazil – a scoping review

Abstract: Asthma is a chronic respiratory disease that can occur in horses of different breeds and ages. While its occurrence has been reported in many countries, its occurrence across Brazil is unclear. This review aimed to gather information about equine asthma from studies performed in Brazil by different groups and investigate a variety of horse populations. Articles published in peer-reviewed scientific journals, as well as information contained in dissertations and theses, were searched on PubMed, SciELO, Google S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Corroborating the case described by Moreira et al (2004), the initial diagnosis of the horse in this report was equine asthma, a relatively common condition in several regions of the country (Oliveira et al, 2022). In Brazil, a large country with different climatic conditions, several studies have described chronic lung conditions related to the different stages of equine asthma (Melo et al, 2007;Oliveira et al, 2022), resulting in the disease being the main suspect in cases of chronic respiratory disease in sport animals.…”
Section: /8supporting
confidence: 72%
See 2 more Smart Citations
“…Corroborating the case described by Moreira et al (2004), the initial diagnosis of the horse in this report was equine asthma, a relatively common condition in several regions of the country (Oliveira et al, 2022). In Brazil, a large country with different climatic conditions, several studies have described chronic lung conditions related to the different stages of equine asthma (Melo et al, 2007;Oliveira et al, 2022), resulting in the disease being the main suspect in cases of chronic respiratory disease in sport animals.…”
Section: /8supporting
confidence: 72%
“…In Brazil, a large country with different climatic conditions, several studies have described chronic lung conditions related to the different stages of equine asthma (Melo et al, 2007;Oliveira et al, 2022), resulting in the disease being the main suspect in cases of chronic respiratory disease in sport animals. The classic manifestation of equine asthma varies from exercise intolerance to dyspnea during rest, in addition to chronic cough, mucous to mucopurulent nasal discharge (Melo et al, 2007;Oliveira et al, 2022), findings compatible with those reported by the owner in the present report and also present in cases of fungal pneumonia (Higgins & Pusterla, 2006).…”
Section: /8mentioning
confidence: 99%
See 1 more Smart Citation